Pemanfaatan Chlorella sp. Untuk Menyisihkan Nitrogen Total Pada POME Dengan Variasi Laju Alir Gas CO2 Menggunakan Flat-Photobioreactor - Meisy Dhyta Amelia; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
POME contains organic matter that can be utilized by microalgae Chlorella sp. Organic material is used as a source of nutrition for growth so as to reduce the content of pollutants in POME. In this research measurements of the growth rate of microalgae Chlorella sp. cells and removal of Total Nitrogen. The research was conducted in batch using flatphotobioreactors with variations in the CO2 gas flow rate was 0,4 L/min; 0,6 L/min; and 0,8 L/min and contact time 0, 1, 3, 5, and 7 days. Based on the results of the research, the highest growth rate of Chlorella sp. cells and the best efficiency of total nitrogen removal were at the CO2 gas flow rate was 0,6 L/min on the seventh day was 0.381/day and 84.4% Keywords: Chlorella sp., POME, CO2 Gas Flow Rate, Flat-Photobioreactor, CO2 absorbed